FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN AIR BERSIH PDAM DI DESA ILOHUNGAYO KECAMATAN BATUDAA KABUPATEN GORONTALO - Ramlah Alkatiri; Harijono Imbran; Desitawati K Agase (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2019)
This research was conducted in Ilohungayo Village, Batudaa District, Gorontalo District. The purpose of this study is to test simple linear regression showing that the income variable has an influence on the demand for clean water (PDAM). This can be seen the regression coefficient test of 0.041, the variable number of family members has a positive and significant influence on the demand for clean water (PDAM). This can be seen from the regression coefficient test of 0.170, while the water tariff variable has a positive influence on the demand for clean water for PDAM. This can be seen from the regression coefficient test of 0.024, percent. Keywords: Income, Number of Family Members, Water Rates and PDAM Water Demand